2021
DOI: 10.2174/1570180817999201001155032
|View full text |Cite
|
Sign up to set email alerts
|

Chalcones and Bis-Chalcones Analogs as DPPH and ABTS Radical Scavengers

Abstract: Background: A number of synthetic scaffolds along with natural products have been identified as potent antioxidants. The present study deals with the evaluation of varyingly substituted, medicinally distinct class of compounds “chalcones and bis-chalcones” for their antioxidant potential. Methods: In vitro radical scavenging activities were performed on a series of synthetic chalcones 1-13 and bis-chalcones 14- 18. Results and Discussion: All molecules 1-18 revealed a pronounced 2-diphenyl-1-picrylhydrazyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Researches on chalcone derivatives reported that chalcones have high antioxidant activity (91,92) .Since antioxidants have the ability to donate electron, it can neutralize the free radical and prevent any damage to biological compound in the body (93) . As chalcones are known as minor flavonoids (94) , they can scavenge free radicals (92) .…”
Section: Aspirin-chalcone Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches on chalcone derivatives reported that chalcones have high antioxidant activity (91,92) .Since antioxidants have the ability to donate electron, it can neutralize the free radical and prevent any damage to biological compound in the body (93) . As chalcones are known as minor flavonoids (94) , they can scavenge free radicals (92) .…”
Section: Aspirin-chalcone Derivativesmentioning
confidence: 99%
“…Researches on chalcone derivatives reported that chalcones have high antioxidant activity (91,92) .Since antioxidants have the ability to donate electron, it can neutralize the free radical and prevent any damage to biological compound in the body (93) . As chalcones are known as minor flavonoids (94) , they can scavenge free radicals (92) . Excess of free radicals and ROS (reactive oxygen species) in human body may cause diseases like cancer, cardio, and cerebrovascular due to damage to lipids, proteins, and nucleic acids (95) .…”
Section: Aspirin-chalcone Derivativesmentioning
confidence: 99%
“…Chalcones are used in several biosynthetic pathways as initial intermediate structures in the production of flavonoids, isoflavonoids, and aurones . A significant part of medicinal chemistry research in the 21st century has been focused on both natural and synthetic chalcones because of their various pharmacological potential including activities and characteristics such as antibacterial, anti-inflammatory, analgesic, , anticholinergic, antiplatelet, antiulcer, antioxidant, , antimalarial, anticancer, , antiviral, antileishmanial, antidiabetic, , immunomodulatory, , aldose reductase inhibition, estrogenic, acetylcholinesterase inhibition, and as non-purine xanthine oxidase inhibitors . Chalcones are highly attractive molecules because of their simple structure, ease of construction, and promising biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In addition to these, there are many studies in the literature showing that bischalcone compounds have various biological activities such as antibacterial and antioxidant activity. [14][15][16][17][18] The biological evaluation of the synthetic and isolated bichalcones reported that the inhibitory investigation of bichalcones against enzymes caused medicinal products, such as anti-browning substances, to be discovered and harmful bacteria and insects to be controlled. [11,13,19,20] The in vitro antiplasmodial activities of a series of bichalcones were reported against the erythrocytic stages of Plasmodium falciparum, and some of them displayed remarkable antiplasmodial activity sensitive to Pf3D7 with IC50 values of 1.5-2.5 mM.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Therefore, concerning the pharmacological significance of bichalcones, we wanted to synthesize a novel series of methoxy-substituted bichalcones with identical substitutions at various positions on the phenyl ring (A) of chalcones. First, we investigated the in vitro antimicrobial potencies of the synthesized bichalcones (10)(11)(12)(13)(14)(15)(16)(17)(18) against Gram-positive and Gram-negative bacteria and yeast and then determined the antioxidant activity of all the synthesized compounds (10)(11)(12)(13)(14)(15)(16)(17)(18) with DPPH and FRAP methods.…”
Section: Introductionmentioning
confidence: 99%